Oxygen demand, uptake and deficit during a sprint time trial in steep uphill cross-country skiing - Hallén, J.; Myklebust, H.; Losnegard, T. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
INTRODUCTION: A significant anaerobic contribution is expected in sprint skiing. Anaerobic energy production during supramaximal exercise has been estimated from the accumulated oxygen deficit (AOD) method in different sports, but not in cross-country skiing. We wanted to use the AOD method to estimate the contribution of aerobic and anaerobic energy sources during a cross-country sprint leg.